Providing a molecular mechanism for P-glycoprotein; why would I bother?. (9th October 2015) - Callaghan, Richard
Abstract : It is almost 40 years since the drug efflux pump P-glycoprotein (permeability glycoprotein or P-gp) was shown to confer multi-drug resistance in cancer cells. This protein has been one of the most extensively investigated transport proteins due to its intriguing mechanism and its affect in oncology. P-gp is known to interact with over 300 compounds and the ability to achieve this has not yet been revealed. Following the binding of substrate and nucleotide, a complex series of conformational changes in the membrane and cytosolic domains translocates substrate across the membrane. Despite over 30 years of biochemical investigation, the availability of structural data and a plethora of chemical tools to modulate its function, the molecular mechanism remains a mystery. In addition, overcoming its activity in resistant cancer cells has not been achieved in the clinic, thereby garnering some degree of pessimism in the field. This review highlights the progress that has been achieved in understanding this complex protein and the value of undertaking molecular studies.